Multidrug-resistant organisms in refugees: prevalences and impact on infection control in hospitals - Heudorf, Ursel; Albert-Braun, Sabine; Hunfeld, Klaus-Peter; Birne, Franz-Ulrich; Schulze, Jörg; Strobel, Klaus; Petscheleit, Knut; Kempf, Volkhard A. J.; Brandt, Christian (German Medical Science GMS Publishing House, 2016)
Introduction: The refugee crisis is a great challenge to the social and healthcare system in European countries, especially in Germany. An abundance of data has been published on the refugees' health problems (infections as well as physical diseases and psychiatric problems) and their prevention (i.e., sanitary and vaccination programs). However, data on prevalences of multidrug-resistant organisms (MDRO) in refugees are scarce, although it is known that most refugees are from or travelled through countries with high prevalences of MDRO. This paper presents current data on MDRO colonization of refugees admitted to hospitals, and the impact of screening upon admission and infection control in hospitals is discussed.Methods: Anonymous data obtained by screening upon hospital admission were reported by hospitals in the Rhine-Main region of Germany to the local public health department. Screening and microbiological analyses were performed from December 2015 to March 2016 according to standardized and validated methods.Results: 9.8% of the refugees screened (32/325) exhibited colonization with methicillin-resistant (MRSA), and 23.3% of the refugees (67/290) were colonized with Gram-negative bacteria with extended spectrum beta-lactamases, and/or enterobacteria with resistance against 3 or 4 groups of antibacterials, so-called 3MRGN (multidrug-resistant Gram-negative bacteria with resistance against penicillins, cephalosporins and quinolones) and 4MRGN (with additional resistance against carbapenems). Carbapenem-resistant Gram-negative bacteria (CRGN) were detected in 2.1% (6/290) of the refugees.Conclusion: The data confirms the studies published between 2014 and 2016, encompassing refugees tested in Germany, the Netherlands and Israel, with prevalences of MRSA and CRGN up to 13.5% and 5.6%. The MDRO prevalences are higher than those of "risk groups" for MRSA, such as hemodialysis patients and patients depending on outpatient home-nursing care or residing in nursing homes. Therefore, screening and special infection control in hospitals is strongly suggested when refugees are admitted to hospitals, in order to ensure best medical practice and safety for all hospital patients regardless of their country of origin.